Understanding drivers of illiberal entrenchment at critical junctures: institutional responses to COVID-19 in Hungary and Poland. (September 2021) - Hajnal, György; Jeziorska, Iga; Kovács, Éva Margit
The present article aims to improve understanding of institution formation in (former) liberal-democratic polities characterized by autocratization tendencies. We examine how the critical juncture created by the COVID-19 pandemic was used, as well as the interplay between antecedent, structural conditions and the particular combinations of political agency and contingency. By comparing the two similar cases of Hungary and Poland – the two European Union countries that have progressed the farthest towards illiberal transformation – and using documentary and interview evidence, we conclude that: (1) whereas Hungary exhibited significant institutional changes, Poland did not; (2) these differences in institutional outcomes can be significantly attributed to differences in certain critical antecedent conditions; and (3) the ability of key political actors – Hungary's Viktor Orbán and Poland's Jarosław Kaczyński – to control their own political camp seems to have exerted an unmistakable effect as well. Points for practitioners The build-up and entrenchment of institutions of illiberal rule in (previously) liberal-democratic contexts are encumbered by diverse political and institutional constraints. External shocks, such as the COVID-19 crisis, may offer an opportunity to bypass those constraints and to change institutions permanently. Our study concludes that the extent to which such historical windows of opportunity can indeed be used to achieve lasting institutional changes depends not only on the objective, historically given political and institutional constraints that illiberal reforms face, but also on their subjective ability to act in a controlled, coordinated and coherent manner.